Oxidative behaviour of four Malaysian edible plant extracts in model and food oil systems - Jaswir, Irwandi; Octavianti, Fitri; Hendri, Ridar; ., Elmi; Khatib, Alfi (Academic Journals, 2012)
The present study was conducted to investigate the antioxidative behaviour of four local plant extracts in Malaysia-- red spinatch (Amarantus gangeticus), “kucai” (Allium odorum), Chinese cabbage (Brassica chinensis), and “kesom” (Polygonum minus)-- in palm olein system and in a linoleic acid model system. The antioxidative capacities of these local plants were then compared to the activity of rosemary and sage, two types of antioxidant commonly found in the market. From the analysis using Oxigen Consumption Method, it was found that among the samples evaluated, red spinatch had the longest time to reach the 50% oxygen in the chamber, with 110 min, meaning that this sample had the highest level of antioxidative activity. This was followed by the extracts of Chinese cabbage (80 min), “kucai” (60 min), and “kesom” (40 min). The antioxidative activities of these plants, however, were lower than those of rosemary and sage. These commercial antioxidants were found to have 150 and 130 min time, respectively, to reach the 50% oxygen in the chamber. Results from differential scanning calorimetry (DSC) analysis showed that addition of red spinatch and Chinese cabbage extract samples to the oil in the system reduced the oxidation as evidenced by longer To of antioxidants-treated samples. The onset time (To) of the oxidation reaction corresponded closely to the intersection of the extrapolated baseline and the tangent line (leading edge) of the exotherm, meaning that the longer To, the greater the antioxidative activity of a sample. Statistical analysis from this study showed that there was no significant difference between To of red spinatch and those of rosemary and sage. This meant that the antioxidative activity of red spinacth samples was comparable to the activities of rosemary and sage. The antioxidative activities of Chinese cabbage, “kucai” and “kesom” were also much higher than that of control. The finding from this study indicated that all samples used in this study had very good potential to be explored as sources of natural antioxidants.